Giant volume magnetostriction in CMR manganites R1-xSrx MnO3 (R = Sm, Nd) - Abramovich, A. I.; Michurin, A. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Magnetization, ac initial magnetic susceptibility, resistance, magnetoresistance, thermal expansion and magnetostriction measurements were performed for R1-xSrxMnO3 (R=Sm, x=0.33, 0.40, 0.45; R=Nd, x=0.33, 0.45)compounds. For all compounds in the TC region we have observed a large volume contraction DV/V» 0.1% and unusual behavior of the volume magnetostriction w, namely, a peak of anomalous magnitude of negative volume magnetostriction on the w(T) curve. We have obtained a giant negative volume magnetostriction 5×10-4 at a relatively low magnetic field B=0.9 T and 10-3 at a high magnetic field B=13 T for Sm samples. The magnetostriction of Nd compounds is one order of magnitude less. For all compounds the giant magnetostriction is accompanied by colossal negative magnetoresistance equal to 78, 72, and 44% at B=0.9 T for Sm compounds with x=0.33, 0.40, and 0.45, respectively. All of the observed properties are explained in the framework of an electronic phase separation model.